2022
DOI: 10.1186/s13098-022-00849-2
|View full text |Cite
|
Sign up to set email alerts
|

Toll like receptor 4 gene Asp299Gly polymorphism increases the risk of diabetic microvascular complications: a meta analysis

Abstract: Objective The relationship between Toll like receptor 4(TLR4) gene Asp299Gly polymorphism and diabetic microvascular complications (DMI) is unclear. Therefore, the aim of this meta analysis was to explore the relationship between TLR4 Asp299Gly polymorphism and DMI. Methods System search PubMed, Web of science, Springer, Cochrane library, ELSEVIER, Wanfang database, VIP, CNKI, a case–control study of the correlation between TLR4 gene Asp299Gly poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…A combined study of the SNPs rs11536889, rs4986790, and rs4986791 revealed that they may increase the risk of T2DM [63]. A recent meta-analysis evaluated the risk of diabetic microvascular complications and found that rs4986790 SNP was associated with T2DM, particularly in patients with diabetic retinopathy [64].…”
Section: Discussionmentioning
confidence: 99%
“…A combined study of the SNPs rs11536889, rs4986790, and rs4986791 revealed that they may increase the risk of T2DM [63]. A recent meta-analysis evaluated the risk of diabetic microvascular complications and found that rs4986790 SNP was associated with T2DM, particularly in patients with diabetic retinopathy [64].…”
Section: Discussionmentioning
confidence: 99%
“…Дослідження стверджують, що генетична схильність може бути одним із факторів, які викликають очні ускладнення ЦД2 [12][13][14]. Розглядаючи роль TLR4 в ДР, кілька дослідників зосередили увагу на асоціації поліморфізмів гена TLR4 й ризику розвитку ДР [14][15][16]. Так, виявлено, що поліморфізми гена TLR4 асоціюються з підвищеним ризиком серцево-судинних захворювань і діабетичної ретинопатії в пацієнтів із ЦД2 [15,16], тоді як за іншими даними мають протективний ефект [17].…”
Section: ключові словаunclassified
“…Генетична схильність є одним із головних чинників, що викликають очні ускладнення ЦД2 [6,7]. Досить добре описа-на асоціація поліморфізмів гена TLR4 і ризику розвитку ДР, при цьому деякі поліморфізми не мають зв'язку, інші збільшують ризик, а деякі ризик ДР зменшують [8][9][10].…”
unclassified